Principles of information systems - Stair, Ralph M.; Reynolds, George Walter 1944- (Course Technology, Cengage Learning, 2014)
"Help your students gain the foundation they need to better understand the IS discipline and how IS courses relate to the rest of their business courses. This edition from authors and practitioners Ralph Stair and George Reynolds focuses on today's core IS principles that are most important for every business student to know. Your students will gain a strong understanding of the changing role of today's IS professional with this book's wealth of current examples and IS references. New detailed coverage of multimedia in business, application development for the iPhone, iPad, and similar devices, cloud computing and updates of forecasting demonstrate issues reshaping IS today. New materials and examples on environmental design and green computing prepare students for today's workplace. New examples of supply chain management (SCM) and customer relationship management (CRM) better equip your students for business success. This edition presents some of the most recent research on virtual communities and work structures, including how social networking sites, such as Facebook and Twitter, are assisting virtual teams and how companies are effectively using virtual organizational structures with mobile workers. Count on Stair/Reynolds' Principles of Information Systems, 10e to provide the insights students need to function more efficiently and effectively as workers, managers, decision makers, and organizational leaders in business today"--Publisher